2014
DOI: 10.1002/cphc.201301176
|View full text |Cite
|
Sign up to set email alerts
|

Clusters of Ammonium Cation—Hydrogen Bond versus σ‐Hole Bond

Abstract: MP2/6-311++G(d,p) calculations were performed on the NH4 (+) ⋅⋅⋅(HCN)n and NH4 (+) ⋅⋅⋅(N2 )n clusters (n=1-8), and interactions within them were analyzed. It was found that for molecules of N2 and HCN, the N centers play the role of the Lewis bases, whereas the ammonium cation acts as the Lewis acid, as it is characterized by sites of positive electrostatic potential, that is, H atoms and the sites located at the N atom in the extension of the HN bonds. Hence, the coordination number for the ammonium cation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 72 publications
1
12
0
Order By: Relevance
“…In all cases, the ammonium cation displays a net charge that is significantly reduced from its formal value of + 1, with the experimental electron density giving the best match to the calculated limit value of approximately + 0.87 e in its clusters. [33] Even when aware of a known fallacy of atomic charges, especially in relation to s-hole interactions, [10] one can still view the modest charge transfer from the chloride anion to the ammonium cation in NH 4 Cl ( % 0.2-0.4 e) as an indicator of rather weak hydrogen bonds between them, [47] which may be quantified from the topological analysis of an electron density distribution by using the above-mentioned Espinosa's correlation. [30,31] Topological analysis of the total of five electron densities (Table 2) within the AIM theory [29] gives much more consistent results than was observed for the net atomic properties (charges and volumes).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…In all cases, the ammonium cation displays a net charge that is significantly reduced from its formal value of + 1, with the experimental electron density giving the best match to the calculated limit value of approximately + 0.87 e in its clusters. [33] Even when aware of a known fallacy of atomic charges, especially in relation to s-hole interactions, [10] one can still view the modest charge transfer from the chloride anion to the ammonium cation in NH 4 Cl ( % 0.2-0.4 e) as an indicator of rather weak hydrogen bonds between them, [47] which may be quantified from the topological analysis of an electron density distribution by using the above-mentioned Espinosa's correlation. [30,31] Topological analysis of the total of five electron densities (Table 2) within the AIM theory [29] gives much more consistent results than was observed for the net atomic properties (charges and volumes).…”
Section: Resultsmentioning
confidence: 97%
“…Black points designate the extremes of electrostatic potential at H and N atoms, which are 0.286 and 0.263 a.u., respectively. [33] (Reprinted with permission from Ref. [33].)…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Similarly, only a relatively few studies of pnicogen-bonded anionic and cationic complexes have been reported in the literature [23][24][25][26][27][28]. We recently reported two systematic studies of cationic P···N pnicogen-bonded complexes.…”
Section: Introductionmentioning
confidence: 93%